IMPLEMENTASI PEMBELAJARAN LEARNING BY DOING DALAM MELATIH KEPERCAYAAN DIRI ANAK DI TK PGRI TUNAS 83 - Arrobi, Jimatul; Toni Sonjaya; Renda Disya Sopani; Dini Haryani; Santi Jumiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The social-emotional development of early childhood depends on a confident character. On the other hand, the phenomenon that occurred at PGRI Tunas 83 Kindergarten showed that students experienced self-confidence issues, characterized by shyness, dependence on teachers, and fear of trying new activities. The purpose of this study was to demonstrate the effectiveness of the learning-by-doing method in increasing children's self-confidence through real-life activities and experiences. This study used a descriptive qualitative methodology. The research subjects consisted of 29 students, with 12 children with low self-confidence as the main subjects. Observation, in-depth interviews, and documentation were used to collect data. To calculate the percentage increase in children's development, the data analysis technique used the Miles and Huberman model, supported by simple descriptive statistical analysis. The study showed that learning-by-doing, such as planting activities, conducting science experiments, and making art with loose parts media, increased children's self-confidence. Quantitatively, there was a significant increase in which 10 of the twelve children (83.3%) in the focus group showed positive behavioral changes. The overall level of students' self-confidence increased from 58.6% to 93.1%. Active activities that engage both physically and mentally can help children become more independent and responsible. In short, a learning-by-doing approach allows children to build independence through real-life success.